THE INFLUENCE OF PREGNANT WOMEN'S KNOWLEDGE ABOUT THE USE OF INSECTICIDAL MOSQUITO NETS ON THE INCIDENCE OF MALARIA BY READING POCKET BOOKS AT PUSKEMAS SENTANI - Flora Niu; Yeni Wardhani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Background: Malaria is an infectious disease caused by Plasmodium, which is a one-celled living creature that belongs to the group of protozoa, malaria is transmitted through the bite of a female anopheles mosquito containing plasmodium in it, plasmodium carried through mosquito bites will live and multiply in human blood cells. Pregnant women belong to the group that is prone to malaria due to the decrease in various pathological conditions in pregnant women and the fetuses they contain. The implementation of malaria control towards elimination is carried out gradually from one island or several islands until all islands are covered in order to realize a healthy living community and free from malaria transmission until 2030. The use of insecticidal mosquito nets is one of the preventive efforts towards malaria elimination. Public knowledge, especially pregnant women, about the use and benefits of insecticidal mosquito nets is an obstacle. Objective: Knowing pe. Methods : The design of this study is an experimental research with a type of quasy experiment with the approach of One Group Pre Test / Post Test Design. The population in this study was pregnant inu who visited the Sentani Health Center with sampling techniques using Non Probability Sampling selected by Perposive Sampling consisting of 30 respondents. The variable measured in this study is the knowledge of pregnant women. This study used the Wilcoxon signed rank test (a<0.05). Result: The results showed that pregnant women's knowledge about the use of berymunu berisktiside after being carried out was higher than before. with a value of p=0.005. Thus it can be concluded that the accepted hypothesis means that there is an influence of the knowledge of pregnant women on the use of insecticidal mosquito nets. Conclusion : there is an influence of pregnant women's knowledge on the development of the use of synsecticide mosquito nets. keywords : Knowledge, Insecticidal Mosquito Nets